THE EFFECT OF ALTRUISTIC LEADERSHIP ON SERVICE INNOVATION AND THE MEDIATION ROLE OF AFFILIATED HUMOR (CASE STUDY OF PEKANBARU AULIA HOSPITAL) - Hafiza Fajrin; Adi Rahmat; Ririn Handayani; Arizal N (Universitas Lancang Kuning, 2022)
This study discusses the influence of altruism leadership on service innovation and the mediating role of affiliate humor at Aulia Hospital. The population of this study were nurses, totaling 70 people. The research data was taken using a questionnaire, with a Likert scale of 1 to 7. The method of data analysis in this study was descriptive quantitative using WarpPLS for testing a hypothesis and testing the validity and reliability of the research instrument. The results showed that altruistic leadership is directly related to service innovation in hospitals with a significant p-value. while the mediating role of affiliation between the effects of altruistic leadership and service innovation is not significant